2015
DOI: 10.1002/jctb.4635
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemical oxidation and biological processes for herbicide degradation

Abstract: BACKGROUND Fenton and photo‐Fenton processes were explored as photochemical pre‐treatments to improve the biodegradability of wastewater containing atrazine, a commercial pesticide. The effects of H2O2, Fe3+ and irradiation level on the degradation processes were studied and the optimal conditions determined. RESULTS Fenton and photo‐Fenton oxidation systems were able to remove 85 and 100% of atrazine, respectively, in a 120 min period. These processes produced a biocompatible solution, removing 100% of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The latter is then effectively treated via a biological process using a pure strain bacterium, Klebsiella terragena . Benzaquén et al showed that Fenton or electro‐Fenton pre‐treatments of wastewater containing atrazine, followed by a biological step, lead to complete mineralization. Thus, atrazine is removed by Fenton oxidation, while residual cyanuric acid is biologically oxidized with a degradation rate of 95 %.…”
Section: Chemical Oxidation Pre‐treatment Followed By a Biological Stepmentioning
confidence: 99%
“…The latter is then effectively treated via a biological process using a pure strain bacterium, Klebsiella terragena . Benzaquén et al showed that Fenton or electro‐Fenton pre‐treatments of wastewater containing atrazine, followed by a biological step, lead to complete mineralization. Thus, atrazine is removed by Fenton oxidation, while residual cyanuric acid is biologically oxidized with a degradation rate of 95 %.…”
Section: Chemical Oxidation Pre‐treatment Followed By a Biological Stepmentioning
confidence: 99%
“…The potential effects of these emergent contaminants in water are still uncertain and further investigation is needed to improve their efficient removal from water. Advanced Oxidation Processes (AOPs) are efficient and effective technology for water treatment that allow the total or partial removal of recalcitrant organic pollutants resistant to conventional treatments (Benzaquén et al 2013;Pignatello et al 2006;Benzaquén et al 2015). Among the various AOPs, heterogeneous Fenton like process in combination with UV-vis light is highly efficient in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various AOPs, heterogeneous Fenton like process in combination with UV-vis light is highly efficient in wastewater treatment. These processes involve the generation of the hydroxyl free radical, which has a very high oxidation potential, by means of the use of strong oxidants (H 2 O 2 ), radiation ultraviolet, and catalysts (Benzaquén et al 2015;Chu et al 2007). The so-called heterogeneous Fenton-like systems use a solid catalyst in the presence of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Partly for this reason, most attempts to develop photocatalytic systems to treat dye-containing wastewater have focused on sequential coupling approaches [2327,14]. A major complicating factor is that dye-containing wastewater often contains refractory and/or inhibitory organic compounds in a biodegradable matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, photocatalytic systems are indiscriminate; it is difficult to ensure that energy is not wasted by generating a series of products that are excessively oxidized or not readily biodegradable [ 21 , 22 ]. Partly for this reason, most attempts to develop photocatalytic systems to treat dye-containing wastewater have focused on sequential coupling approaches [ 23 27 , 14 ]. A major complicating factor is that dye-containing wastewater often contains refractory and/or inhibitory organic compounds in a biodegradable matrix.…”
Section: Introductionmentioning
confidence: 99%